DESIGN OF COMPOSITE SKIN PANEL FOR ROOF IN ACCORDANCE WITH THE REQUIREMENTS OF EN 1995-1-1 AND GSN В.1.2-2:2006 (Academic journal Industrial Machine Building Civil Engineering, 2019)
In the article design of composite (timber and plywood) skin panel has been considered according European and nationalstandards. The panel consists of timber webs and plywood skin. The design parameters are depth of webs and distance between webs within the defined skin parameters. In design the method of fictitious cross-section is applied. Check of the ultimate limit states is conducted in accordance with EN 1995-1-1 (ДБН В.2.6-161:2017). Loads to the panel are determined according to ДБН В.1.2.-2:2006. The usage of European and national standards complies with the actual requirements andwiden methodological base.
Keywords: roof members; two-sided composite skin panel; design of building constructions; loads on building constructions